?CONDENSATION OF SOME HETARYL SUB- STITUTED DIKETONES WITH AROMATIC DIAMINE: ?Short Communication (Biological Sciences - PJSIR, 2003)
The condensation of 1,2-di(quinolyl-2)-1,2 ethanedione and 1,2-di(6-methylquinolyl-2)-1,2-ethanedione with 4-methyl 1,2- phenylenediamine in the presence of acetic acid results in the formation of 2,3-di(quinolyl-2)-6-methylqui-noxaline and 2,3-di(6-methylquinolyl-2)-6-methylquinoxaline, respectively.